2005
DOI: 10.1007/s00244-004-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Antifouling Booster Biocides in Water and Sedimentfrom the Port of Osaka, Japan

Abstract: Concentrations of booster antifouling compounds in the port of Osaka, Japan were assessed. Concentrations of Sea-Nine 211 (4,5-dichloro-2-n-octyl-3-isothiazolone), thiabendazole (2-(4-thiazolyl)-benzimidazole), IPBC (3-iodo-2-propynyl butylcarbamate), Diuron (3,4-dichlorophenyl-N, N-dimethylurea), Irgarol 1051 (2-methylthio-4-t-butylamino-6-cyclopropylamino-s-triazine), and M1 (2-methylthio-4-t-butylamino-6-amino-s-triazine) in port water samples were in the range of <0.003-0.004 microg L(-1), <0.0008-0.020 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…As a result of legislation restricting the use of TBT-based antifouling paints, some reduction in the levels of TBT has been reported, particularly in areas proximate to recreational shipping activities (Rees et al 2001;Hawkins et al 2000). However, in areas near industrial shipping activities (e.g., ports), TBT levels remain high (Valkirs et al 2003;Peachery 2003;Horiguchi et al 2004;Harino et al 2006). South Africa is positioned along a primary shipping route between Europe, the Americas, and Asia.…”
Section: The Regulation Of Organotin Compoundsmentioning
confidence: 95%
“…As a result of legislation restricting the use of TBT-based antifouling paints, some reduction in the levels of TBT has been reported, particularly in areas proximate to recreational shipping activities (Rees et al 2001;Hawkins et al 2000). However, in areas near industrial shipping activities (e.g., ports), TBT levels remain high (Valkirs et al 2003;Peachery 2003;Horiguchi et al 2004;Harino et al 2006). South Africa is positioned along a primary shipping route between Europe, the Americas, and Asia.…”
Section: The Regulation Of Organotin Compoundsmentioning
confidence: 95%
“…Therefore, environmental scientists have analyzed residue levels of suspected antifouling agents to investigate their potential use in Japan. Detection of Irgarol 1051 (Irgarol), its metabolite, and Diuron in water samples collected from coastal marinas, fishery harbors, and ports has provided information on their possible use in antifouling paints on ships and boats in Japan [6][7][8][9]. Meanwhile, the "International convention on the control of harmful anti-fouling systems on ships, 2001 (IMO Convention)" was adopted at the International Maritime Organization (IMO) diplomatic conference held in October 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Carbendazim residues were detected in surface water samples in Chile [11]. Thiabendazole residues have been detected in citrus samples [12], in fruit-based soft drinks [13], in apple juice concentrate [14], in lemons [15], in water samples [16], in sea port water and in sediment samples [17], in foodstuffs [18], in the UK mushroom industry [19]. Furthermore, Thiabendazole application creates eco-toxicity, for instance, Castillo et al [20] found a macroinvertebrate community changes following thiabendazole applications in a banana plantation.…”
Section: Introductionmentioning
confidence: 99%